Algoma-type Neoproterozoic BIFs and related marbles in the Seridó Belt (NE Brazil): REE, C, O, Cr and Sr isotope evidence. (August 2015) - Sial, Alcides N.; Campos, Marcel S.; Gaucher, Claudio; Frei, Robert; Ferreira, Valderez P.; Nascimento, Rielva C.; Pimentel, Marcio M.; Pereira, Natan S.; Rodler, Alexandra
Abstract: The Jucurutu Formation in the Seridó Belt, northeastern Brazil, encompasses fine-to coarse-grained amphibolite-facies marbles, locally with cross-bedding and stromatolites. Banded iron formations (BIF) at three localities in this belt comprise itabirites (actinolite- or cummingtonite-itabirite and quartz-hematite itabirite) and iron ores, which are overlain by marbles of the Jucurutu Formation. Diamictites of uncertain stratigraphic position in the Seridó Belt exhibit gneiss and quartzite clasts up to 0.6 m long and a fine-grained metapelitic matrix. The C-isotope stratigraphic pathways for the Jucurutu Formation show negative δ 13 C values at the base of the formation followed upsection by positive values. At the Ferro do Bonito iron Mine, values as low as −12‰ in carbonates just above the contact with underlying BIF are followed by values of ca. −5‰ and by positive values up section (+4 to +10‰). δ 13 C values for carbonates of the Jucurutu Formation deposited on top of BIFs at the Riacho Fundo, São João do Sabugi, and Serra da Formiga sections are all positive, the contact surfaces between carbonates and BIFs being covered by weathered material. The 87 Sr/ 86 Sr values for carbonate rocks of the Jucurutu Formation are mostly in the 0.7074–0.7075 interval, a ratio commonly observed in the late Cryogenian to the early Ediacaran. The studied BIFs exhibit Cr concentrations one magnitude higher than usual and largely unfractionated Cr isotope composition, similar to average magmatic values. They are characterized by δ 53 Cr values between −0.42 and −0.12‰, by Ce anomalies (Ce/Ce*) ranging from −0.4 to 0.7, by positive Eu anomalies, and by super-chondritic Y/Ho ratios (>20). The combination of geochemical parameters and association with mafic rocks resemble Algoma-type BIFs. These BIFs possibly formed proximally to hydrothermal vents, in anoxic and acidic deep waters, whereby Fe and Cr were leached from mafic or ultramafic rocks. High concentrations of Cr in the BIF with a magmatic inventory isotope composition, together with pronounced positive Eu anomalies, fit a rift depositional scenario, characterized by narrow basins and strong hydrothermal input, in which anoxic (ferruginous) conditions prevailed. This is substantiated by the occurrence of positive Ce anomalies. Their deposition was followed by carbonates which show "normal" Cr concentrations with slightly positively fractionated δ 53 Cr values. These carbonates may represent post-glacial cap carbonate sequences deposited in an anoxic to slightly oxic shallow marine environment, as suggested by Ce/Ce* versus Pr/Pr* and Ce/Ce* versus Nd cross-relationships. Graphical abstract: Highlights: Ediacaran BIFs of the Jucurutu Fm. (Seridó Belt) are assigned to the Algoma type. BIFs show positive Eu and Ce anomalies, high Cr contents and negative δ 53 Cr values. Overlying marbles show less negative δ 53 Cr, δ 13 C from −6 to 10‰, 87 Sr/ 86 Sr ∼ 0.7075.